KOMITE FARMASI NASIONAL (KFN), KONSIL KEFARMASIAN, KONSIL TENAGA KESEHATAN INDONESIA (KTKI) - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2022)
This research was made with the aim of discussing and reviewing the differences between the National Pharmacy Committee (KFN), the Pharmacy Council and the Indonesian Council of Health Workers (KTKI). This study uses a normative juridical method. The data used is secondary data, which is based on the laws and regulations that apply as primary legal material. The analysis was carried out qualitatively by reviewing the legal norms regulated in the laws and regulations to then draw conclusions from the results of the analysis. The results of the analysis show that there is no connection and legal relationship between KFN and the Pharmaceutical Council or KTKI. The Pharmacy Council itself is part of the KTKI